HUBUNGAN PERAN PERAWAT DALAM EMPOWERING DAN ENABLING DENGAN PERAN ORANG TUA DALAM PERAWATAN ANAK SAKIT USIA 4-6 TAHUN - ULVA NOVIANA; Heni Ekawati (NHM PRESS, 2021)
The role of parents is the acceptance of the child's condition and provides participation in care.The form of participation is that parents are expected to live with children, behave well and be involved in care. Based on the results of the preliminary study found that 4 parents had a good role in child care at the hospital, and 5 parents had sufficient roles in child care at the hospital, while 1 parent had a lack role in child care in the hospital.The purpose of the study is to analyze the relationship between the role of nurses in the application of Family Centered Care (Empowering and Enabling) and the role of parents in caring for children who are sick aged 4-6 years at the hospital.The research design used was analytical, namely with a cross sectional approach. The independent variable in this study was the role of nurses in Empowering and Enabling (Family Centered Care) and the dependent variable in this study was the role of parents in the care of sick children.The total population were 80 respondents and the sample size were 67 respondents. The technique of taking used simple random sampling, the instrument used was a questionnaire and the statistical test used was Spearman Rank with a significance value of α 0.05.This research as been carried out ethical clearance test by the KEPK Ngudia Husada Madura. The results of the 67 respondents found the role of nurses with the role of parents has a value of p value of 0.030 <0.05, with a value of r = 0.266 so H1 wasaccepted there was a relationship between the two variables. The results of this study are expected to be more maximal role of nurses in enabling parents in the process of caring for their children while being hospitalized so that the impact on the role of parents in caring for their children during hospital